Stress and active control analysis of functionally graded piezoelectric material cylinder and disk under electro-thermo-mechanical loading. (March 2018) - Parhizkar Yaghoobi, Mohammad; Ghaffari, Iman; Ghannad, Mehdi
The purpose of this article is to investigate the active control behavior and stress analysis of functionally graded piezoelectric material circular hollow cylinder and disk under electro-thermo-mechanical loading. Also, this research presents a new compact formula for analysis of cylinder and disk that could be useful for engineers and designers to get insight into behavioral change of structures by geometry. The exact solutions of the functionally graded piezoelectric material structures could be found based on Lame's solution. For a radially polarized cylinder and disk with continuously graded properties, it is assumed that material properties are varied by a power-law function, and inner surface and outer surface of these structures are considered to be sensor and actuator, respectively. Based on the exact solution, extensive numerical analyses are carried out to provide an insight into the effect of non-homogeneity constant and control factor on electro-thermo-mechanical behaviors and active control analysis of structures. The results show how the electro-thermo-mechanical behaviors change by non-homogeneity and control factor.